Pemberdayaan Kelompok Tani Jaya Bersama Melalui Inovasi Pembibitan Kopi dengan Ekstrak Bawang Merah dan Metode Setek - Apriantonedi, Reko; Fransisko, Eko; Effendi, Darwan; Fernandes, Regi; Parwito, Parwito (Jurnal Pengabdian, 2024)
This service aims to increase the knowledge and skills of the Jaya Bersama Farmer Group in Tanjung Dalama Village, South Curup Subdistrict, Rejang Lebong Regency, in coffee breeding using the cuttings method by giving onion extract as a root growth stimulant. The implementation method was carried out through a series of theoretical and practical training, focusing on the coffee seedling stage. Farmer groups were involved in intensive counselling and training activities, including the delivery of theory on coffee seedling, demonstration of the application of the cuttings method, and application of shallot extract. Furthermore, a field practice session was held at the farmer group leader's house. The results showed a significant improvement in the Jaya Bersama Farmer Group's understanding and skills related to coffee breeding using the cuttings method and onion extract application. They were able to apply these techniques well, producing high-quality coffee seedlings that have the potential to increase the productivity and income of the farmer group as a whole. Thus, this service successfully empowered the farmer group through innovation in their farming practices.